(untitled) (Orfeu, 2017)
The formal structure in the four movements of Villa-Lobos’s Eighth String Quartet (1944) reveals his concern to reinterpret classical form (sonata form, andante, minuet/scherzo, and sonata rondo) according to the post-tonal harmony he developed during the 1920s. This study investigates the correlations between harmony and form, interpreting some analogies apparently made by Villa-Lobos to emulate points of formal articulation as seen in classical music. The employment of some peculiar chord structure, with recurrence of interval symmetry instead of the traditional tonality, indicated that an analytical approach based on set theory would be more adequate to this analysis.